Antidepressant activity of flavones from traditional Chinese medicine: a meta-analysis - Qing Wang; Youyuan Lu; Xue Mi; Caiyan Yang; Wei Ma; Changbo Xia; Hanqing Wang (Pharmaceutical Biology)
Context Flavones, the key active components in Traditional Chinese Medicine (TCM), have demonstrated antidepressant activity. Given the numerous animal studies conducted, a systematic analysis is essential to provide a valuable reference for future research.Object This study investigated the antidepressant activity of flavones based on animal models and summarized the underlying mechanisms.Methods We systematically searched 7 bibliographic Databases as of August 12, 2023, such as Web of Science, PubMed, China National Knowledge Infrastructure, etc. The meta-analysis was performed using either the random or fixed-effect model, supplemented by trial sequential analysis (TSA). The Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach was used to assess the quality of evidence.Results A total of 25 studies involving 458 mice were included, identifying five flavones (baicalin, baicalein, apigenin, luteolin, vitexin) with antidepressant activity. Compared to the control group, flavones significantly reduced immobility time in forced swimming and tail suspension tests. Flavones also decreased serum and hippocampal levels of interleukin (IL)-1β and tumor necrosis factor-alpha (TNF-α), reduced nuclear factor kappa B (NF-κB) levels, and increased brain-derived neurotrophic factor (BDNF) levels. Relative to the positive group, flavones raised IL-6, sucrose preference rate, and corticosterone (CORT) levels, with no significant differences in other factors. The TSA showed the efficacy of flavones for treating depression with adequate ‘information size’ for the primary outcome.Conclusions The results demonstrate that flavones exert protective effects against depression in mice, primarily by stimulating neurotrophic factors and modulating inflammatory pathways. These findings emphasize their potential as promising candidates for the development of novel antidepressant therapies.